Pengaruh Good Corporate Governance Dan Budaya Organisasi Yang Berbasis Tri Hita Karana Terhadap Kinerja Lembaga Perkreditan Desa (LPD) Di Kecamatan Abiansemal - Darmawati, Ni luh Adi; Ayu, Putu Cita; Pramuki, Ni Made Wisni Arie (Hita Akuntansi dan Keuangan, 2024)
This study aims to further examine the Influence of Good Corporate Governance and Tri Hita Karana-Based Organizational Culture on the Performance of Village Credit Institutions (LPD) in Abiansemal District. This research was conducted at the Village Credit Institution (LPD) in Abiansemal District by distributing research questionnaires to 96 respondents who were involved in this study. The data analysis method used is SEM PLS with the help of Smart PLS software. The results showed that the performance of the LPD in Abiansemal Badung District was influenced by an organizational culture based on tri hita karana. As well as in this study, good corporate governance has a positive but not significant influence on LPD performance. It is suspected that the LPD in the Abiansemal sub-district has not been able to implement good corporate governance maximally, which is a factor influencing the performance of the LPD itself.